Észak-Bácska sorsa 1944/45-ben - Forró, Lajos (Közép-Európai Közlemények, 2011)
The attrocities against the 1944/45 Hungarians in Vojvodina started in the 90s. There were no possibilities to do researches in the Central Achives, nevertheless numerous works on local history came to light that were mostly based on the stories of the witnesses. The opportunity to look into the documents of the Vojvodian Achives made it possible to state the data precisely and to compare them. In the documents of the Vojvodian Achives there are many uncorrect personal names, mixed place names. It needed precise and thorough research to make the documents useful for the science of history. In the article I compare the local researces from Magyarkanizsa, Martonos, Oromhegyes and Adorjan with the documents of the Vojvodian Achives. Thanks to that new data and names came to light. In Magyarkanizsa 17, in Martonos 8, in Oromhegyes 2 new, until now unknown names of victims turned up. In Adorjan there is a unique judgement in which the murderers are found guilty. Fond number 183, that contains the documents of the above mentioned places consists of 549 boxes , 24 boxes of disordered documents and 79 books. Resaearchers has not finished the examination of these documents yet. With further researches new names and data could also turn up.